IL PROGETTO SISMA AL XX SALONE DELL’ARTE DEL RESTAURO E DELLA CONSERVAZIONE DEI BENI CULTURALI E AMBIENTALI DI FERRARA - de Biase, Alfredo (Archeomatica, 2013)
La presenza dell'Associazione Alternativa Arte al XX Salone dell'Arte del Restauro e della Conservazione dei Beni Culturali e Ambientali di Ferrara ha oltrepassato le più rosee aspettative, inserendosi come evento importante nel variegato e attraente panorama degli eventi organizzati al Salone. ABSTRACT The presence of the Association Alternative Art in XX Fair Art of Restoration and Conservation of Cultural and Environmental Heritage has exceeded all expectations, fitting as cult event in the diverse and attractive view of events on the cultural heritage present in the exhibition. The Association of Alternative Art in the show has set up a photo exhibition entitled "Emilia Romagna - Earthquake 2012" with photos taken directly from the president, arch. Alfredo de Biase, during the work of securing the cultural heritage affected by the earthquake in the areas of Modena. Given that this year's Salone was principally concerned with calamitous event that has affected the cultural heritage of Emilia Romagna, is understandable as photos of de Biase have been the backdrop to the whole event, so that they were included in the offi cial logo of the 'event. Within the exhibition space the interest of visitors and various newspapers television is directing it, as well as view the pictures, the screening of the video, produced by fi lmmaker Sergio Grillo for Ce.Se.Vo.Ca., covering activities by Alternative Arts and in particular those relating to the Project Earthquake (Progetto Sisma).